2020
DOI: 10.2147/jpr.s274225
|View full text |Cite
|
Sign up to set email alerts
|

<p>Upregulation of μ-Opioid Receptor in the Rat Spinal Cord Contributes to the α2-Adrenoceptor Agonist Dexmedetomidine-Induced Attenuation of Chronic Morphine Tolerance in Cancer Pain</p>

Abstract: Background: Sustained morphine treatment for cancer pain has been limited due to analgesic tolerance. Opioid receptor internalization and desensitization mediated by downregulation of mu-opioid receptor (MOR) expression have been confirmed as one of the mechanisms of chronic morphine tolerance. In addition to the opiate system, the α2-adrenergic system is involved in the development of morphine tolerance. Several studies reported that co-administration of α2-adrenoceptor agonist dexmedetomidine inhibits morphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Hyperalgesia due to sustained use of morphine is a causative factor of opioid analgesic tolerance. [38,39] In our study, the combination of CXCL12 with morphine accelerated the development of morphine-induced hyperalgesia, similar to the results of a translational study showing a reduction in the maximal possible antinociceptive effect in rats pretreated with CXCL12 compared with that in those administered morphine alone. [23] Inhibition of CXCL12/CXCR4 by co-administering CXCL12-Ab or AMD3100 attenuated the progression of hyperalgesia.…”
Section: Discussionsupporting
confidence: 88%
“…Hyperalgesia due to sustained use of morphine is a causative factor of opioid analgesic tolerance. [38,39] In our study, the combination of CXCL12 with morphine accelerated the development of morphine-induced hyperalgesia, similar to the results of a translational study showing a reduction in the maximal possible antinociceptive effect in rats pretreated with CXCL12 compared with that in those administered morphine alone. [23] Inhibition of CXCL12/CXCR4 by co-administering CXCL12-Ab or AMD3100 attenuated the progression of hyperalgesia.…”
Section: Discussionsupporting
confidence: 88%
“…Given that MOR is the most important opioid receptor responsible for the analgesic effect of morphine, numerous studies have focused on the MOR density and function adaptive changes underlying opioid tolerance and dependence [ 30 , 31 ]. However, studies on the regulation of MOR after chronic opioid treatment have given conflicting results, depending on the experimental conditions [ 32 , 33 , 34 ]. Our present results showed that the expression of MOR was decreased in the spinal cords of BCP rats, and such a decrease was much more obvious in the BM group.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we did not enroll patients taking opioids. Thus, we can exclude a reduction of the opioid receptor reserve as a consequence of desensitization and/or internalization of MOR ( Zhang and others 2020a ). Still, several questions are open.…”
Section: The Impact Of Exogenous Opioids On the Immune System In Cp C...mentioning
confidence: 99%